Impact of socioeconomic status on survival following ST-elevation myocardial infarction in a universal healthcare system. (1st February 2019) - Steele, Lloyd; Palmer, James; Lloyd, Amelia; Fotheringham, James; Iqbal, Javaid; Grech, Ever D.
Abstract: Background: Lower socioeconomic status (SES) has been associated with worse outcomes after acute myocardial infarction. Data for survival after ST-elevation myocardial infarction (STEMI) by SES in the current era of primary percutaneous coronary intervention (PCI) is more limited. Methods: Data was collected for all patients with acute STEMI undergoing primary PCI at The South Yorkshire Cardiothoracic Centre, UK between 2009 and 2014. A Cox regression analysis was used to assess differences in survival by SES quartile (using an area-level measure). Results: Of the 3126 STEMI patients, 2655 (84.9%) were first presentations of STEMI. Lower SES groups generally had a less favourable baseline cardiovascular risk factor profile, with higher rates of smoking (p = 0.001), diabetes (p = 0.007) and previous coronary heart disease (p = 0.025). With the exception of beta-blockers, the use of secondary preventative medications was similar between SES quartiles. Adjusting for age and gender, the most disadvantaged SES quartile trended to a non-significant increased mortality at 30 days (hazard ratio 1.35 (0.79–2.33)), 1 year (1.12 (0.76–1.65)), or 3 years (1.22 (0.88–1.70)) compared to the least disadvantaged SES quartile, but this was attenuated by adjusting for additional cardiovascular risk factors and medication use on discharge. Conclusions: In this large study of unselected STEMI patients managed by primary PCI, we did not find any significant differences in survival by SES at 30 days, 1 year, or 3 years. Highlights: Lower socioeconomic status is associated with worse outcomes post-MI. STEMI and NSTEMI are managed different, with urgent reperfusion needed for STEMI. Lower socioeconomic groups have greater use of emergency services. Data for survival after STEMI by socioeconomic status in the era of PCI is limited. We did not find any significant differences in survival by SES.